Sustainable Investment Strategies: An Analyzing the Interplay Between ESG Ratings, Dividend Policy, Financial Performance, and Investor Trust - Rudianto, Pandef; Darmono, Darmono; Tontowi, Arif Jauhar (International Journal of Business, Law, and Education, 2024)
This study investigates the interplay between Environmental, Social, and Governance (ESG) ratings, dividend policy, financial performance, and investor trust. Using data from publicly listed firms, the research examines how ESG performance influences dividend policies and financial outcomes, and how these, in turn, affect investor trust. The results reveal a significant positive relationship between ESG ratings and all dependent variables, with dividend policy serving as a mediator in the ESG-investor trust linkage. Firms with higher ESG ratings demonstrate better financial performance, stable dividend payouts, and increased investor confidence. These findings underscore the strategic importance of ESG integration for enhancing financial stability and market perceptions. The study contributes to the literature by elucidating the mechanisms through which sustainability practices drive corporate success and provides actionable insights for corporate managers, investors, and policymakers.